Does aprotinin reduce lung reperfusion damage after cardiopulmonary bypass? - Rahman, A; Üstünda, B; Burma, O; Özercan, IH; Çekirdekçi, A; Bayar, MK (Elsevier Science Bv, 2000)
Objective: The role of aprotinin in the prevention of lung reperfusion injury was investigated in the patients undergoing cardio-pulmonary bypass (CPB) for coronary artery bypass grafting (CABG) operations. Methods: The study was planned randomly and prospectively. Two hundred milliliters of physiological saline solution was added to the prime solution of patients in group I (n = 10) whereas, 200 mi aprotinin (Trasylol. Bayer AG) was given to patients in group II(n = 10). In order to measure lung tissue malondialdehyde (MDA) levels, glutathion peroxidase (GSH-Px) activity levels and polymorphonuclear leukocytes (PMNs) numbers, lung tissue samples were taken before CPB and 5 min after removing the cross clamp. In addition, alveolo-arterial oxygen difference (AaDO(2)) for tissue oxygenation was calculated by obtaining arterial blood gas samples. Results: MDA levels before CPB increased from 41.72 +/- 21.00 nmol/g tissue to 66.71 +/- 13.44 nmol/g tissue in group I and from 43.44 +/- 5.16 nmol MDA/g tissue to 53.22 +/- 10.95 nmol MDA/g tissue in group II after cross clamp removal (P = 0.001 and P = 0.021, respectively). The increase in group LI was found to be significantly lower than group I (P = 0.048). With the initiation of reperfusion. GSH-Px activity decreased in group I from 3.05 +/- 0.97 to 2.31 +/- 0.46 U/mg protein (P = 0.015) whereas GSH-P,: activity in group II decreased from 3.18 +/- 1.01 to 2.74 +/- 0.81 U/mg protein (P = 0.055). This decrease in the group II was less than group I (P = 0.049), AaDO(2) significantly increased in the group I and II (P = 0.012 and P = 0.020, respectively), but elevation in the group I was significant than in the Group IT (P = 0.049). In histopathological examination: it was observed that neutrophil counts in the lung parenchyma rose significantly following removal of cross clamp in both groups (P = 0.001). The increase in group I was significantly larger than in group II (P = 0.050). Conclusion: Results represented in our study indicate that addition of aprotinin (2 million units) into the prime solution during CPB can reduce lung reperfusion injury. (C) 2000 Elsevier Science B.V. All rights reserved.
5th National Congress of Thoracic and Cardiovascular Surgery -- OCT 20-24, 1998 -- ANTALYA, TURKEY
Keywords: aprotinin; cardio-pulmonary bypass; reperfusion injury; lung